FLIPPED CLASSROOM TEACHING VOCABULARY FOR THE YOUNG LEARNERS - Yakupova Kamila (Journals Park Publishing, 2023)
Flipped classroom is effectively for the learners so that in this article is devoted to the flipped classroom in teaching vocabulary for the young learners and the concept of flipped classroom of thoughts and different ways of teaching techniques of flipped classroom not only for the young learners but also all the teaching process.